Tingkat Hiperemesis Gravidarum pada Ibu Hamil Trimester I di Kabupaten Kendal - Arisdiani, Triana; hastuti, Yuni Dwi (Jurnal Kebidanan Malakbi, 2020)
Hyperemesis gravidarum is excessive or uncontrollable vomiting during pregnancy, which causes dehydration, electrolyte imbalance, or nutritional deficiencies. If this situation gets worse and cannot be overcome, it will endanger the mother and the fetus. The purpose of this study was to determine the description of the hyperemesis gravidarum of pregnant women in the first trimester in Kendal Regency. Descriptive research design using a non-probability sampling design with a total sample of 54 pregnant women with gestational age 0-12 weeks who conducted pregnancy checks at the Polindes, Nolokerto Village, Kaliwungu District, Kendal Regency. The research instrument used a Check List. Data analysis using percentage. The results showed that almost all respondents (92.6%) had mild hyperemesis gravidarum, and a small proportion (7.4%) of respondents had moderate hyperemesis. It can be concluded that most of the trimester 1 pregnant women have hyperemesis gravidarum. It is recommended that pregnant women and their families actively seek information regarding the handling of hyperemesis gravidarum.